Promoting the Aging Process and Enhancing the Production of Antioxidant Components of Garlic through Pulsed Electric Field Treatments - Chao-Kai Chang; Sheng-Yen Tsai; Ming-Shiun Tsai; An-Ting Tu; Chih-Yao Hou; Kuan-Chen Cheng; Wei-Lun Zhu; Rizka Mulyani; Chang-Wei Hsieh (MDPI AG, 2024)
Shortening the aging duration and enhancing the functional components of garlic present significant technical challenges that need to be addressed. Thus, this study aimed to evaluate the potential role of pulsed electric field (PEF) treatment, a novel nonthermal food processing method, in promoting and enhancing the functional attributes of aged garlic. Our results showed that 2-4 kV/cm PEF pretreatment increased S-allyl cysteine (SAC), total polyphenol (TPC), and flavonoid contents (TFC) compared with un-pretreated garlic during aging. The browning and texture-softening were also significantly improved during processing time, though the latter showed no significant difference from the eighth day to the end of the aging process. The principal component analysis results showed that PEF positively affects the SAC and TFC formations without adverse effects. Among the PEF pretreatments, 3 kV/cm is the most effective in enhancing functional component production compared with the other PEF pretreatments. Therefore, PEF pretreatment is a time-saving process that promotes and enhances the functionality of aged garlic.